ANALYSIS OF THE ROLE OF PARENTS IN OVERCOMING IMPACT HOSPITALIZATION IN PRE-SCHOOL AGE CHILDREN AT KARDINAH HOSPITAL TEGAL - Gayuh Siska Laksananno; Sadar Prihandana; Agus Mulyadi (Prodi D3 Keperawatan Tegal Poltekkes Kemenkes Semarang, 2021)
Preschool age children will feel that being sick and being cared for is a form of punishment for children, because moral development is oriented towards punishment and obedience. Children who are cared for are considered as an event that can create stress in children. Stressors received by children during treatment can be in the form of an unfamiliar hospital environment, physical conditions such as pain and illness experienced, treatment procedures, and medical examinations. This can cause sleep disturbances, decreased appetite, and developmental disorders, so it can slow down the healing process. The results of the study at Raden Mattaher Hospital Jambi, found that 46.7 child respondents behaved poorly during the action and as many as 53.3% of the children showed good behavior during the action, with 36% of the respondents not accompanied by their parents and 63.3% accompanied by their parents during the action. Poor behavior shows the child being more aggressive, kicking, screaming. Parents as the closest people to children, have an important role in the hospitalization of children. The role of parents that can be done while the child is hospitalized is for parents to establish communication and collaboration with the health profession. The purpose of the study was to determine the relationship between parental participation and the impact of hospitalization on preschool-aged children who were treated at the hospital. The design of this study was a correlation study with a cross sectional approach which was conducted on 72 respondents. The research instrument used a questionnaire on the impact of hospitalization and parental participation which had been tested for validity and reliability. The results of the study found that there was no significant relationship between respondent characteristics, parental characteristics and parental participation with the impact of hospitalization. Suggestions, it is necessary to prepare both physically and psychologically so that parental participation can be carried out properly. Nurses in the pediatric ward should foster better relationships with parents and children and for policy makers in hospitals should establish policies in the implementation of nursing care involving parents Keywords: pre-school age children; participation of parents; impact of hospitalization